Resilience for working in Ontario home and community care: registered practical nurses need the support of themselves, family and clients, and employers - Denise M. Connelly; Anna Garnett; Kristin Prentice; Melissa E. Hay; Nicole A. Guitar; Nancy Snobelen; Tracy Smith-Carrier; Sandra M. McKay; Emily C. King; Jen Calver; Samir Sinha (BMC, 2024)
Abstract Background The context of practice is often not explicit in the discourse around the personal and professional resilience of nurses. The unique factors related to providing nursing care in home and community care may provide novel insight into the resilience of this health workforce. Therefore, this research addressed how nurses build and maintain resilience working in the home and community care sector. Method A qualitative study was conducted between November 2022 to August 2023 using 36 in-depth interviews (29 registered practical nurses [RPNs], five supervisors of RPNs, two family/care partners (FCPs) of clients receiving home and community care services). Analysis was consistent with a grounded theory approach including coding and comparative methods. Results The factors of personal and professional resilience were not distinct but rather mixed together in the experience of nurses having resilience working in the home and community care sector. The process of building and maintaining resilience as home and community care nurses was informed by three categories: (1) The conditions of working in HCC; (2) The rapport RPNs held with FCPs; and (3) The nurses' ability for supporting the 'self'. Multiple components to inform these categories were identified and illustrated by the words of the nurse participants. Conclusion The process of building and maintaining resilience by RPNs working in the home and community care sector was guided by the day-to-day experiences of providing care for clients and the conditions of being a mobile health care provider. However, nurses may sense when they need to support their 'self' and must be empowered to request and receive support to do so.